2007
DOI: 10.1007/s10592-007-9373-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant genetic admixture after reintroduction of peregrine falcon (Falco peregrinus) in Southern Scandinavia

Abstract: The peregrine falcon (Falco peregrinus) population in southern Scandinavia was almost extinct in the 1970's. A successful reintroduction project was launched in 1974, using captive breeding birds of northern and southern Scandinavian, Finnish and Scottish origin. We examined the genetic structure in the pre-bottleneck population using eleven microsatellite markers and compared the data with the previously genotyped captive breeding population and contemporary wild population. Museum specimens between 53 and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…, Jacobsen et al . , Johnson et al . ), and have attributed this result most often to Wahlund's effect, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Jacobsen et al . , Johnson et al . ), and have attributed this result most often to Wahlund's effect, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…, Jacobsen et al . , Johnson et al . ), we assumed that this was a statistical artefact of conducting multiple comparisons and both loci were retained in subsequent analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Although microsatellite estimates cannot be easily compared among species due to the application of different loci and variable sample sizes, we can extract important conclusions at the species level. For instance, Jacobsen et al. (2008) and Brown et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2007) showed that Scandinavian and North American populations of peregrine falcons, respectively, have not experienced significant loss of genetic variability after recent contaminant‐induced population bottlenecks (see Table S2). It has been argued (Jacobsen et al. , 2008) that the current levels of genetic diversity in recovered Scandinavian and some North American populations are unexpectedly high due to introgression following the introduction of captive‐bred peregrine falcons, some of which were not native subspecies (Enderson et al.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases Swindell and Bouzat (2006b) these populations have limited reproductive potential, requiring intensive management, e.g., through captive breeding programs and translocations, to ensure their persistence and long-term viability. Translocation programs in the Florida panther and the Mexican wolf (Hedrick and Fredrickson 2010), Greater prairie-chickens (Bouzat et al 2009), bighorn sheep (Hogg et al 2006), and the Peregrine falcon in southern Scandinavia (Jacobsen et al 2008), emphasize the potential benefits and pitfalls of genetic rescue (see also Tallmon et al 2004;Edmands 2007).…”
Section: Purging and Extinctionmentioning
confidence: 99%